2019
DOI: 10.1039/c9cc08294h
|View full text |Cite
|
Sign up to set email alerts
|

Covalently assembled dopamine nanoparticle as an intrinsic photosensitizer and pH-responsive nanocarrier for potential application in anticancer therapy

Abstract: A covalently assembled dopamine nanoparticle is constructed to serve as an intrinsic photosensitizer and pH-responsive drug nanocarrier for combined PDT and chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(35 citation statements)
references
References 25 publications
0
35
0
Order By: Relevance
“…It is worth noting that targeting an acidic tumor microenvironment is quite a versatile approach for anticancer therapy and has been successfully employed not only for VCC but also for other carriers, e.g. polymeric nanoparticles; 105 this supports the potency of this strategy. The pH sensitivity of VCC crystals limits their oral administration (at least if the crystals are not functionalized) due to the swift VCC dissolution and the loss of the payload in the stomach (pH B 1.5-3.5).…”
Section: Caco 3 and Its Polymorphsmentioning
confidence: 64%
“…It is worth noting that targeting an acidic tumor microenvironment is quite a versatile approach for anticancer therapy and has been successfully employed not only for VCC but also for other carriers, e.g. polymeric nanoparticles; 105 this supports the potency of this strategy. The pH sensitivity of VCC crystals limits their oral administration (at least if the crystals are not functionalized) due to the swift VCC dissolution and the loss of the payload in the stomach (pH B 1.5-3.5).…”
Section: Caco 3 and Its Polymorphsmentioning
confidence: 64%
“…Min et al reported another approach for PS loading using UCN@mSiO 2 for RB encapsulation in its porous shell layer. [64,86] At 980 nm irradiation, the RB-loaded UCN core emitted luminescence at 540 nm, which was effectively transferred for RB [ 289] MSN (Alkylthioethene) ZnPc (525) Naphthalene dye [ 159] Liposome Tetraphenylchlorin Paclitaxel (Thioether) [ 290] Crosslinked polymer Poly(dopamine) (635) Bortezomib (Catechol-boronate) [ 291] Disassembly Liposome (Dehydrocholesterol) Tetraphenylporphyrin (420) Dehydrocholesterol endoperoxide [ 292] Polymer micelle (Alkoxyanthracene) Eosin Y (525) Mitoxantrone [ 117] Polymer micelle (Alkoxyanthracene) Anthracene (365) DOX [32] Polymer micelle (Thioether) Ce6 (660) DOX [ 115] Polymer micelle (Propylene sulfide) Chlorin e6 (670) DOX [ 116] Polymer micelle PPIX (635) SN38 (Thioether) [ 293] Polymer micelle Porphyrin (400) Se (Diselenide) [ 294] Polymer micelle Poly(fluorine-benzothiadiazole) (Vis) Vancomycin, PMB [ 303] RGD-targeted polymer micelle Indocyanine (660) Camptothecin [ 295] UCN@PEI Curcumin (432; 980) Curcumin [ 308] UCN@mSiO 2 UCN (980); RB (540) RB [64,86] UCN yolk-shell UCN (980); RB, hematoporphyrin (540) RB, hematoporphyrin [64] UCN@Au/TiO 2 UCN (980); TiO 2 (NIR) Ampicillin [ 310] UCN@poly(vinylpyrrolidone) UCN (980); ZnPc ZnPc [ 301] UCN@chitosan UCN (980); ZnPc ZnPc [ 309] activation for ROS production and disassembly. This accounted for a potent antibacterial activity against MRSA and extended spectrum beta-lactamase-producing E. coli.…”
Section: Ros Disassembly By Upconversion Luminescencementioning
confidence: 99%
“…[ 6–9 ] PDA has been applied in the biomedical field that for drug delivery, bioimaging, and tissue engineering biosensing applications. [ 10–12 ] Because of its specific structure, PDA is capable of loading antitumor drugs (such as doxorubicin (DOX)) via π–π stacking or hydrogen bonding interactions, with loading rates as high as 91%. Surprisingly, in addition to its strong ability to adsorb drugs, PDA is effective in releasing drugs by internal stimulation (hydrogen peroxide) or from an external stimulus (near‐infrared (NIR) irradiation), reducing the toxic effects of chemotherapeutic drugs.…”
Section: Introductionmentioning
confidence: 99%